Novel cryoballoon system for pulmonary vein isolation: multicenter assessment of efficacy and safety - The ANTARCTICA study. (19th May 2022) - Heeger, CH; Pott, A; Sohns, C; Sommer, P; Tondo, C; Fassini, G; Bohnen, J; Dahme, T; Rillig, A; Wakili, R; Metzner, A; Tilz, RR
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary vein isolation (PVI) either by balloon devices or point by point radiofrequency (RF) and 3D mapping based catheter ablation forms the cornerstone of invasive atrial fibrillation (AF) treatment and has demonstrated high procedural success and encouraging long-term outcomes. Although equally effective cryoballoon (CB) based PVI offers shorter procedure duration as well as lower complication rates compared to RF based PVI. Beside the worldwide established Arctic Front Advance (AFA) cryoablation system a novel CB ablation system, POLARx was recently introduced. The POLARx CB incorporates unique features which may translate into improved efficacy and safety of CB based PVI. However, multicenter assessment of periprocedural efficacy and safety is lacking up to date. Methods: From August 5th to october 12th 2020, a total of 317 patients with paroxysmal or persistent atrial fibrillation (AF) underwent POLARx CB based PVI in 5 centers from Germany and Italy. Acute efficacy and safety were assessed. Results: In 317 patients (mean age 64±12 years, 209/317 (66%) paroxysmal AF) a total of 1256 pulmonary veins (PV) were identified and 1252 (99, 7%) PVs were successfully isolated utilizing the mainly the short tip POLARx CB (82%). The mean minimal cryoballoon temperature was -57.9±7 °C. Real-time PVI was visualized in 72% of PVs. The mean procedure time 92±41 minutes with a mean fluoroscopy time of 15±10 minutes. Concerning periprocedural complications 1 (0.3%) cardiac tamponade successfully treated by pericardial puncture and 4 (1.3%) pericardial effusion without any intervention were detected. A total of 13 phrenic nerve injuries (4.1%) occurred during treatment of the right superior PV (9/13) and right inferior PV (4/13). Phrenic nerve injury recovered in 3/13 (23%) patients until discharge. Two minor bleeding of the groin (0.6%), 1 (0.3%) severe bleeding with intervention, 5 transient air embolism (1.6%) and 3 (0.9%) stroke / TIA has been observed. Conclusions: In this large multicenter assessment the novel POLARx CB shows a promising efficacy and safety profile. Further studies are necessary to draw final conclusion.